Inhibition of Fap Promotes Cardiac Repair by Stabilizing BNP. Issue 5 (9th February 2023) - Sun, Yuxi; Ma, Mengqiu; Cao, Dandan; Zheng, Ancheng; Zhang, Yiying; Su, Yang; Wang, Jianfang; Xu, Yanhua; Zhou, Mi; Tang, Yansong; Liu, Yifan; Ma, Teng; et al.
Abstract : Background: Myocardial infarction (MI) elicits cardiac fibroblast activation and extracellular matrix (ECM) deposition to maintain the structural integrity of the heart. Recent studies demonstrate that Fap (fibroblast activation protein)—a prolyl-specific serine protease—is an important marker of activated cardiac fibroblasts after MI. Methods: Left ventricle and plasma samples from patients and healthy donors were used to analyze the expression level of FAP and its prognostic value. Echocardiography and histological analysis of heart sections were used to analyze cardiac functions, scar formation, ECM deposition and angiogenesis after MI. RNA-Sequencing, biochemical analysis, cardiac fibroblasts (CFs) and endothelial cells co-culture were used to reveal the molecular and cellular mechanisms by which Fap regulates angiogenesis. Results: We found that Fap is upregulated in patient cardiac fibroblasts after cardiac injuries, while plasma Fap is downregulated and functions as a prognostic marker for cardiac repair. Genetic or pharmacological inhibition of Fap in mice significantly improved cardiac function after MI. Histological and transcriptomic analyses showed that Fap inhibition leads to increased angiogenesis in the peri-infarct zone, which promotes ECM deposition and alignment by cardiac fibroblasts and prevents their overactivation, thereby limiting scar expansion. Mechanistically, we found that BNP (brain natriuretic peptide) is a novel substrate of Fap that mediates postischemic angiogenesis. Fap degrades BNP to inhibit vascular endothelial cell migration and tube formation. Pharmacological inhibition of Fap in Nppb (encoding pre-proBNP) or Npr1 (encoding the BNP receptor)-deficient mice showed no cardioprotective effects, suggesting that BNP is a physiological substrate of Fap. Conclusions: This study identifies Fap as a negative regulator of cardiac repair and a potential drug target to treat MI. Inhibition of Fap stabilizes BNP to promote angiogenesis and cardiac repair.